An Analysis of Village Fund Management Implementation Based on the Regulation of the Minister of Internal Affairs Number 20 of 2018 at Tanjung Agung Village of Tanjung Agung Palik Sub-District of North Bengkulu Regency - Hadi Supriyono; Ahmad Soleh; Zahrah Indah Ferina (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The purpose of this research is to describe about the implementation of village financial management according to Minister law number 20 of 2018 at Desa Tanjung Agung, Kecamatan Tanjung Agung Palik North Bengkulu regency. The method which used in this research is interactive analysis. The result shows that the financial managemen has followed the law which mentioned in Peraturan Menteri Dalam Negeri Republik Indonesia No 20 of 2018 about village financial management which involves: 1 a planning of village chamberlain to manage and collect data for a year needs, village held a meeting with village officers, BPD and society to tell them the idea to develop the village for the future. 2) using the village fund was done by using village account, the list of transaction in and out is followed by complete transaction proof and legal. Kaur finance must record all transaction, 3) Kaur finance record all money in and out in general cash book and do closing every end of the month and report it to village secretary to be verified, the secretary tell the chief for the approval. The responsibility report by secretary is always in time and quicker from the deadline which decided before 10th on next month.4) chamberlain create a financial report every one semester, the detail based on the guidelines. The realization report of village APD realization on first semester announced exact time, every second week on July, while the second semester on the fourth week of January next year. Village financial report which reported by chief to the regent followed by subdistrict head consist of the report of village spending realization in procurement of good and service. 5) the responsibility of realization to regent always on time while the report to society through end year meeting and using banner.